2022
DOI: 10.1037/int0000257
|View full text |Cite
|
Sign up to set email alerts
|

Effective and accessible telephone-based psychotherapy and supervision.

Abstract: The COVID-19 pandemic forced clinics to quickly shift service provision and supervision of students to remote operations. Mental health services for people facing barriers, including those who live in extreme poverty, remain a critical need, especially when considering the direct and indirect consequences of a global health crisis. The focus of this paper was to examine the effectiveness of psychotherapy treatment and clinical supervision, via telephone delivery (i.e., audio-only calls), from March to July of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Scores on the WAI-SR started out high and approached the maximum total score by Session 24. Given the possible impact on rapport Rowen et al (2021) found when clinicians used an audio-only modality, it appears that being able to see the clinician may facilitate the ability to build strong rapport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scores on the WAI-SR started out high and approached the maximum total score by Session 24. Given the possible impact on rapport Rowen et al (2021) found when clinicians used an audio-only modality, it appears that being able to see the clinician may facilitate the ability to build strong rapport.…”
Section: Discussionmentioning
confidence: 99%
“…with flexibility to discuss new stressors, especially related to the negative impact of COVID-19. Further information about supervision processes, clinic policies, and procedures for consenting clients can be found in Rowen et al (2021). This study was approved by our university’s Institutional Review Board (Protocol #: 2020-0836).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review highlighted the importance of establishing an open entry system at primary care level for detection and intervention of mental health problems (Yue et al 2020). Two qualitative studies reported telemedicine was more effective when the therapeutic relationship had already been established between clinician and patient (Rowen et al 2021, Verhoeven et al 2020. Patient motivation and careful patient selection is critical, especially for specific interventions such as iCBT (Weineland et al 2020).…”
Section: Barriers and Facilitators To Intervention Implementationmentioning
confidence: 99%
“…Telehealth can be defined as the distribution of services (e.g., health services, supervision, training, and intervention) via electronic platforms and telecommunication technologies (Hames et al, 2020). Telehealth can be utilized to reach long distance patients, educate others, supervise, and reach many groups of people across the world (Hames et al, 2020; Rowen et al, 2022). Due to the COVID‐19 pandemic, many universities and school districts, as well as other providers (e.g., educators and psychological service providers) were required to teach and conduct services via telehealth using various platforms (Bell et al, 2020; Rowen et al, 2022).…”
Section: Postsecondary Educationmentioning
confidence: 99%